Investigation of the potential effects of alpha-lipoic acid on human degenerated intervertebral disc tissue primary cell cultures - Aydın, İrfan; Yaşar Şirin, Duygu; Karaarslan, Numan; Özbek, Hanefi (Turkish Neurosurgical Society, 2022)
AIM: To investigate the supplementation of alpha-lipoic acid (ALA) at the molecular level to determine its effect on primary cell cultures prepared from human intervertebral disc (IVD) tissue in an in vitro environment. MATERIAL and METHODS: Human primary cell cultures were prepared from IVD tissue resected during surgery. While cell cultures without ALA supplementation formed the control group, those with ALA supplementation formed the study group. All cell groups were stained using acridine orange/propidium iodide (AO/PI), and the incidence of apoptotic cell death was determined under a fluorescent microscope. Cell surface morphology and extracellular matrix (ECM) structures were evaluated under an invert light microscope. Simultaneously, cell proliferation was evaluated by MTT–ELISA analysis, and the expressions of chondroadherin (CHAD), cartilage oligomeric protein (COMP), interleukin-1 beta (IL-1?), and matrix metalloproteinase (MMP)-7 and-19, which are genes associated with ECM regulation, were tested using qRT–PCR. The data obtained were evaluated statistically using Tukey’s honestly significant difference (HSD) test after analysis of variance (ANOVA) was performed. The alpha significance value was accepted as <.05. RESULTS: Compared to the cells in the control group, it was observed that both proliferation was suppressed and ECM structures deteriorated in the cells in the study group. CONCLUSION: Also, it was reported that the all-gene expression levels changed. ALA supplementation can negatively affect human IVD primary cell cultures in an in vitro environment.
Keywords: Alpha-Lipoic Acid; Cartilage Oligomeric Matrix Protein; Chondroadherin Gene; Interleukin-1 Beta; Intervertebral Disc; Matrix Metalloproteinase